Entrepreneurial science thinking approach in project-based learning - D K Jamil; M Muslim; B Supriatno (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This 21st century, research and development related learning strategies have been widely implemented, one of which is the use of project-based learning model. This model has a positive effect on student learning outcomes. However, most of the use of this model focuses more on the appropriateness between the concepts and projects the students are working on. This is considered less hope to compete in the 21st century, especially in aspects of life and career skills. Thus, it is necessary to design a learning strategy that facilitates student to use the concepts that they learn to solve daily problems or even entrepreneurship by applying the Entrepreneurial Science Thinking (ESciT) approach. Therefore, this paper will describe the application of the Entrepreneurial Science Thinking (ESciT) approach in project-based learning as a learning strategy that is expected to provide opportunities for students to further improve their skills not only on the mastery of concept but also on life and career skill.